Development of filaments for fused deposition modeling 3D printing with medical grade poly(lactic-co-glycolic acid) copolymers. (21st April 2019) - Feuerbach, Tim; Callau-Mendoza, Sara; Thommes, Markus
Abstract: The manufacturing of custom implants and patient-tailored drug dosage forms with fused deposition modeling (FDM) three-dimensional (3D) printing is currently considered to be very promising. Most FDM printers are designed as an open filament system, for which filaments with a defined size are required. In addition to this processing requirement, the filament material must be of medical or pharmaceutical quality, in order to be suitable in these applications. In this work, filaments with nominal diameters of 1.75 mm and diameter tolerances of ±0.05 mm or lower were developed in a continuous extrusion process. The filaments were made from different medical grade poly(lactic- co -glycolic acid) (PLGA) copolymers. Thermal characterization of the material with differential scanning calorimetry (DSC) showed increased material degradation with increasing hydrophilicity. Mechanical characterization of the filaments showed tensile strengths in the range of 41–48 MPa and Young's moduli in the range of 2055–2099 MPa. Stress relaxation tests showed no irreversible change in filament diameter under processing conditions similar to the utilized 3D printer. Due to unexpected differences in processability in the 3D printer, the molecular weight of the materials was identified as an additional relevant parameter.